Potential for Improving Livelihoods through the Commercial Utilization of Non-Timber Forest Products (NTFPs) in the Target Villages, Xaysomboun Province, Lao PDRoun Province, Lao PDR - VORASANE, houan; WANNENG, Phongxiong; XONG , Si; CHONGVILAI , Aekarthit (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
The aim of this research was to assess the potential uses of Non-Timber Forest Products (NTFPs) in selected developing areas of Xaysomboun Province. The specific objectives were to (1) identify and evaluate potential NTFP species for improved management and production, with the goal of enhancing rural livelihoods, and (2) compare income from NTFP sales with other household income sources. The study employed field-based data collection methods, including structured surveys and group discussions conducted across nine villages in three districts: Anouvong, Thathom, and Hom. A total of 174 households and several district representatives participated in the interviews. Data were analyzed using IBM SPSS Statistics 24, employing techniques such as multiple response analysis, basic descriptive statistics, and Pearson correlation. The results identified 13 high-value commercial NTFP species harvested for trade within the study areas. Among them, Arenga westerhoutii Griffith (locally known as MakTao) showed the highest potential for future promotion, with a suitability rate of 84–100%. Four other NTFP species were classified as having moderate potential, with suitability rates ranging from 50–66%. The NTFP sector contributed significantly to rural livelihoods, providing an average annual income of 11,300,000 Kip per household—just slightly below the income from rubber plantations (11,600,000 Kip). However, agriculture and livestock remained the primary income sources, generating approximately 33,100,000 Kip and 16,700,000 Kip per household per year, respectively. Despite their importance, the abundance of high-value NTFP species has declined significantly over the past 15 years. This decline is attributed to population growth, agricultural land expansion (particularly for rubber and cassava plantations), and inadequate enforcement of forestry laws and regulations.